Increased risk of death from pneumonia among cancer survivors: A propensity score‐matched cohort analysis - Shiori Tanaka; Manami Inoue; Taiki Yamaji; Motoki Iwasaki; Tetsuji Minami; Shoichiro Tsugane; Norie Sawada; the JPHC Study Group (Cancer Medicine, 2023)
Abstract Background The repeated global pandemic of the new virus has led to interest in the possibility of severe pneumonia among cancer patients and survivors. Here, we aimed to assess the association between incident cancer and risk of death from pneumonia in Japanese in a large population‐based cohort study. Methods We used the data from The Japan Public Health Center‐based Prospective Study (JPHC Study), which enrolled subjects aged 40 to 69 between 1990 and 1994 and followed their cancer incidence and mortality until 2013. After identifying 103,757 eligible subjects for analysis and imputing missing data on covariates by the chained equations approach, we conducted propensity score‐matched analysis for 1:4 matching, leaving 14,520 cases diagnosed with cancer and 48,947 controls without cancer during the study period for final analysis. A Cox proportional hazards regression model was used to estimate the hazard ratio (HR) and corresponding confidence interval (CI) for the risk of death from pneumonia with comparison of cancer cases and cancer‐free controls. Results Compared to cancer‐free individuals, risk of death from pneumonia was significantly higher among those who had any diagnosed cancer (HR, 1.41; 95%CI, 1.08–1.84); those within 1 year of diagnosis (HR, 23.0; 95% CI, 2.98–177.3); within 1 to <2 years (HR, 3.66; 95% CI, 1.04–12.9); and those with regional spread or distant metastatic cancer at initial diagnosis (HR, 2.01; 95% CI, 1.26–3.21). A history of lung, oesophageal, and head and neck cancer conferred the higher risk among site‐specific cancers. Conclusion We found a positive association between incident cancer and risk of death from pneumonia in this study. These results imply the possibility that the immunocompromised status and respiratory failure due to antitumor treatment may have resulted in a more severe outcome from pneumonia among cancer survivors than the general population.